Analysis Of Salt Production Location Using The Salt Location Suitability Index To Apply The Continuously Dynamic Mixing In The Greenhouse Salt Tunnel In North Aceh And East Aceh - Andi Kurniawan; Abdul Aziz Amin; Gatot Ardian; Mohamad Zaki Mahasin; Rachmad Dian Kuncoro (Politeknik Kelautan dan Perikanan Dumai, 2021)
One of the main potentials of marine resources in Indonesia is salt. Salt production locations are located in various regions of Indonesia. Aceh Province is one of the leading salt-producing areas on the island of Sumatra. Salt production in Aceh faces various challenges, such as the production system and salt production locations' suitability. Therefore, to develop salt production in Aceh, analysis of the production system and suitability of salt production sites are fundamental. This study aims to analyze the production system and the suitability of salt production locations in North Aceh Regency and East Aceh Regency as salt production centers in Aceh Province. This research uses a combination of qualitative and quantitative methods (mixed method) with a descriptive approach. Production system analysis is carried out through direct observation and in-depth interviews with the stakeholders (government and salt farmers). Analysis of the salt location's suitability level was carried out using the Salt Suitability Index (SSI) method. This study shows that the production system in North Aceh and East Aceh districts uses three production methods consisting of boiling seawater, solar evaporation, and a combination of boiling and solar evaporation. The main obstacle to salt production in Aceh is the weather, such as high rainfall and fluctuations throughout the year. Analysis of the suitability of the location of salt production shows the value of the SSI at the salt ponds site in the North Aceh and the East Aceh Regencies is 80% which indicates that the locations are sufficiently appropriate as a salt production site. The results of this study show that the application of the Continuously Dynamic Mixing (CDM) method in Greenhouse Salt Tunnel (GST) technology may be used to improve the quality and quantity of salt production in Aceh.